Why TVES have contributed to interregional imbalances in China - Ito, Junichi (International Food Policy Research Institute, 2002)
The major objectives of this paper are to shed some light on the mechanism that generates interregional economic imbalances among communities in rural China. Central to this issue is the development of township and village enterprises (TVEs) because the presence of secondary industry is closely associated with the economic welfare of the people residing in rural communities. In rural Jiangsu, for example, spatial disparities have become more pronounced over the past two decades. This fact suggests that the influence of initial conditions—historical and geographical advantages of industrial frontrunners—has not been erased but rather continues to persist. This is attributed to a variety of factors, including the less efficient use of TVE resources in poor areas, the decentralized fiscal system, and agglomeration economies. In short, the socialist regime of self-reliance that still lingers in China’s rural society traps less advanced areas in poverty.